Upregulation of cholesterol storage signalling genes in HEPG2 cells supplemented with edible bird nest (EBN) extract - Tawai, Darreen; Noor, M. A. M.; Salleh, F.; Razak, I. S.; Mansor, R.; Ideris, A.; Md. Ajat, Mohd Mokrish (Faculty of Veterinary Medicine, Universiti Putra Malaysia, 2018)
“Caviar of the East” or better known as Edible-Bird Nest (EBN) is a highly valuable product composed of solidified salivary secretion of a few insectivorous swiftlet species. Swiftlets falls under the family Apodidae and the two main genera with the highest commercial values are Aerodramus (echolating swiftlets) and Collocalia (non-echolating swiftlets). The objective of this study is to determine the qualitative genes expression level associated in lipid signalling pathways such as Acetyl-CoA acetyltransferase 2 (ACAT2), Diacylglycerol O-acyltransferase 2 (DGAT2), Low density lipoprotein receptor (LDLR), Sterol regulatory element binding transcription factor 2 (SREBP2), 3-hydroxy-3-methylglutaryl-CoA reductase (HMGCR), Proprotein Convertase Subtilisin/kexin type 9 (PCSK9) in HepG2 mammalian cell with or without supplementation of EBN extract and exogenous lipid. Raw EBN were manually cleaned, dried in 60°C oven and left overnight. In this project, EBN supernatant were added with acetone using 1:2 ratio and kept in -80°C for an hour. HepG2 mammalian cells were cultured in six wells plates and each wells were treated according to Base Control, Positive Control, Negative Control, Treatment 1, Treatment 2 and Treatment 3. In this study, there were significant differences in terms of genes expression especially in ACAT2 and LDLR genes with supplementation of EBN extract and exogenous lipid concentrate.